Critérios de sustentabilidade socioambiental nas compras públicas: um estudo na Universidade Federal do Tocantins - Santos, Carla Daniele dos (Universidade Federal do Tocantins, 2016)
This study includes three basic concepts: Sustainable Development, Procurement and Public Procurement Sustainable. Reflecting broader concerns about the quality of life and well-being beyond the purely economic approach, the concept of sustainable development won recently high degree of prominence. Given this perspective, it has been included issues related to sustainability in Public Administration management practices. Law No. 12,349 (BRAZIL, 2010) includes as a third legal purpose of bid to promote sustainable national development. The aim of the Sustainable Public Procurement, as a procedure aimed at the inclusion of environmental, social and economic sustainability criteria in government procurement, is to use the significant power of state procurement to influence society and the market. The state as a consumer starts to buy sustainable products and reflects the productive sectors the need for a new commercial approach. This work aimed to study the fulfillment of the social function of the bid as a way to promote sustainable national development through the adoption of social and environmental sustainability criteria in public procurement from the case of the UFT - Federal University of Tocantins through documentary research. There are many barriers to the inclusion of environmental sustainability criteria in public procurement, especially in relation to costs and competitiveness restriction. In the current national scenario of Sustainable Public Procurement sustainable, procurement are still incipient. In the case of UFT were diagnosed good practice about sustainable procurement as the purchase of recycled paper and products, the demand for products made with certified wood, lease printers and vehicles. And they were also diagnosed important points to be improved on the need for revision of the Sustainable Logistics Management Plan and dissemination of results and planning at the operational level of activities related to the procurement process, including the adoption of targeted sustainable criteria not only to products purchased but also in the procurement planning process and demand survey, in checking the greetings of those criteria and life cycle analyzes, such as durability, quality and final disposal. As applied research, were proposed, as a product of this work, guidelines for the creation of a Sustainable Procurement Manual for the Federal University of Tocantins.